CORPORATE GOVERNANCE DAN PERILAKU TAX COMPLIANCE PADA USAHA KECIL DAN MENENGAH - Agusti, Rosalita Rachma; Sanawiri, Brillyanes (Profit: Jurnal Adminsitrasi Bisnis, 2019)
Small and medium enterprises (SMEs) have a very important role in the Indonesian economy. The existence of SMEs in Indonesia is strongly influenced by several factors including those offered by the market and corporate governance. Good corporate governance is an important thing that supports business sustainability. Implementation of corporate governance for SMEs involving entrepreneurs compliance to government regulations, such as regulations related to taxation. Indonesia implement self-assessment system in terms of tax payments and tax reporting. It is confirms that corporate governance and the fulfillment of tax obligations are closely interrelated. Data is collected by interview using in depth interview technique. The results show that business owners have not applied the good corporate governance code for SMEs which prove that tax compliance has not been implemented properly. Based on tax obligation indicators, this study reveal that SMEs implement tax obligations on NPWP ownership, but have not performed other obligations, namely tax payment and reporting.